Solving Infinite Nonlinear Boundary Value Problems of Three Orders by Using Shooting Method - Ahmed Antsar Ghatheth (College of Education for Pure Sciences, 2012)
ABSTRACT The purpose of this research is to design an algorithm for solving nonlinear boundary value problems of third orders with an infinite number of boundary conditions. Newton-Raphson method was used for finding (∞) value then we solved it by using shooting method. good results were obtained with a very small error value.